School orientation game - Low, Jun Wei (2019)
University freshmen orientation camp is one of the most memorable moments a student can remember in his or her experience in university. The highlight of a university freshmen orientation camp includes one or more team building game and the school orientation tour. The team building game can be conducted indoor or outdoor depending on the nature of the game and its purpose is to give enjoyment and opportunities for the freshmen students to bond through teamwork and problem solving. On the other hand, the school orientation tour allows the students to get to know the places which they will frequent throughout their study in the university.